Analisis Penegakan Hukum Pidana Klitih oleh Anak: Studi Kasus Putusan Pengadilan Negeri Yogyakarta Nomor 124/Pid.B/2022/PN Yyk - Antonius Bayu Putra Setiawan (International Forum of Researchers and Lecturers, 2026)
The increasing incidence of klitih involving juveniles in the Special Region of Yogyakarta has created complex legal issues concerning criminal liability and the protection of children's rights within the juvenile justice system. This study aims to analyze criminal law enforcement against juvenile klitih offenders based on Yogyakarta District Court Decision Number 124/Pid.B/2022/PN Yyk, focusing on judicial considerations in determining criminal responsibility and factors influencing law enforcement. This research employs normative-empirical legal research using statutory, conceptual, and case approaches with qualitative analysis. Primary data were obtained through interviews and court decisions, while secondary data were collected from legal literature and legislation. The findings show that judicial considerations primarily focused on juridical aspects, including witness testimony, documentary evidence, and statutory provisions. However, non-juridical aspects, such as the child's psychological condition, family background, social environment, and the best interests of the child, were not comprehensively considered. Law enforcement is influenced by legal substance, law enforcement officials, legal culture, and public perceptions of klitih. Therefore, consistent implementation of restorative justice principles is needed to achieve legal certainty, justice, rehabilitation, and protection of children's rights.